Cannabinoid Hyperemesis Syndrome: A Case Report of Cyclic Severe Hyperemesis and Abdominal Pain with Long-Term Cannabis Use - Julia Hermes-Laufer; Lola Del Puppo; Ihsan Inan; François-Xavier Troillet; Omar Kherad (Case Reports in Gastrointestinal Medicine)
Introduction. Cannabinoid Hyperemesis Syndrome (CHS) is a rare condition that includes cyclic severe vomiting in subjects who have been consuming large doses of cannabis for several years. One of the major diagnostic criteria is the alleviation of symptoms by hot showers. The syndrome was first described in 2004 and is so far neither completely understood nor well known. The latter leads to continued morbidity in concerned subjects and unnecessary expenses for futile investigations. Standard treatments of vomiting as 5-HT3 or D2-receptor antagonists have been shown to be ineffective in alleviating the symptoms. The only long-term satisfying treatment option is the complete abstinence from cannabis consumption. Case Summary. In this case report we describe a 26-year-old male Caucasian long-term cannabis consumer who repeatedly presented in our emergency room with cyclic severe nausea and vomiting ceased by hot showers and resistant to all other treatments. The final diagnosis was not established until his third visit to the ER. Conclusion. CHS is an important differential diagnosis in patients who present with cyclic vomiting and abdominal pain with a history of long-term cannabis use. Recognition of this syndrome is important in order to avoid unnecessary clinical testing and to help the patients break the cycle of drug use.